Assessment of risk factors and clinical effectiveness in the treatment of arterial hypertension in patients with the metabolic syndrome - E. I. Polozova; V. V. Skvortsov; E. V. Puzanova; A. A. Seskina; N. S. Nefedov (Лечащий Врач)
The high prevalence of metabolic syndrome worldwide, the steady growth of morbidity in people of different age groups makes it one of the most serious problems in the clinic of internal diseases, rightfully considering it an epidemic of the 21st century. Taking into account that one of the main components of the metabolic syndrome is arterial hypertension, we studied and assessed the risk factors and effectiveness of the treatment of arterial hypertension in patients with metabolic syndrome. Purpose of the paper: To assess the risk factors and effectiveness of the treatment of arterial hypertension in patients with the metabolic syndrome. The study involved 110 patients with a verified diagnosis of Stage II arterial hypertension and metabolic syndrome. All patients in the study group were treated as inpatients at Saransk Republican Clinical Hospital № 5 during the period 2018-2020. Risk factors were assessed and the treatment of arterial hypertension in patients with metabolic syndrome was analysed. The clinical study showed that the most common risk factors for adverse prognosis in patients with metabolic syndrome and arterial hypertension are psycho-emotional stress, excess body weight, hypodynamia and hereditary burden of arterial hypertension and metabolic syndrome. Inpatient treatment of arterial hypertension in patients with the metabolic syndrome with combined hypotensive therapy was rational in 100% of cases. Inpatient treatment of patients with metabolic syndrome was effective, which was determined by a reduction in blood pressure to the level of target values. The average time of blood pressure reduction in the patients of the analyzed group was 5,86 ± 0,94 days.